Laparoscopic repair of intrathoracic kidney associated with giant congenital diaphragmatic hernia: an infant case report and literature review - Ji, Ze; Zhao, Zhen; Xi, Hongwei; Ren, Hongxia (Frontiers in Pediatrics, 2024)
Background: Intrathoracic kidney (ITK) is a rare congenital disease, with only about 40 pediatric cases reported worldwide to date. ITK associated with congenital diaphragmatic hernia (CDH) is even rarer, and we report a case of an infant with ITK combined with a giant CDH.A six-month-old male infant was hospitalized due to "vomiting for 4 days". The child's parents sought a definitive diagnosis and treatment to alleviate the child's suffering. Following a series of examinations and laboratory tests, we determined the child had ITK combined with CDH. We treated the condition laparoscopically, repairing the diaphragmatic defect and securing the kidney to the posterior wall of the abdomen. After a two-year follow-up period, the child exhibited no significant discomfort.Infantile ITK combined with giant CDH is relatively rare and the etiology is unclear.When symptoms of pneumonia, gastrointestinal obstruction or genitourinary tract occur, surgical intervention is necessary. Laparoscopic reduction of the ectopic kidney and repair of the giant diaphragmatic hernia is a minimally invasive and effective surgical approach.